2005
DOI: 10.1007/s10529-005-8450-3
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oscillating Bioreactor BelloCell: Implications for Insect Cell Culture and Recombinant Protein Production

Abstract: BelloCell is a novel packed bed bioreactor that allows alternating nutrient and gas transfer to a culture. Spodoptera frugiperda Sf-9 grown in the BelloCell (300 ml culture) reached 1.3-1.5x10(7) cells ml-1 in 7-8 days and the total baculovirus-expressed protein yield was 2.3-times that in a stirred tank bioreactor (600 ml culture). The superior cell and protein yields underline the potential of BelloCell for cell culture and recombinant protein production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…An example is the multilayered hyper flasks from Corning ® with scaled-up volume (up to 10 times) on which cells can be grown ( ). Another example is the BelloCell ® from CESCO Bioengineering Inc. ( 44 ). The principle of the BelloCell is that of alternating nutrient and gaseous exchange.…”
Section: Antigen Productionmentioning
confidence: 99%
“…An example is the multilayered hyper flasks from Corning ® with scaled-up volume (up to 10 times) on which cells can be grown ( ). Another example is the BelloCell ® from CESCO Bioengineering Inc. ( 44 ). The principle of the BelloCell is that of alternating nutrient and gaseous exchange.…”
Section: Antigen Productionmentioning
confidence: 99%
“…1A) has a top lid equipped with a 0.22-m pore size filter for ventilation and is prepacked with BioNOC II carriers (CESCO Bioengineering) for cell immobilization (Chen et al, 2005). The compressible lower chamber (i.e., the "bellow") can be alternately compressed and released by the BelloStage (CESCO Bioengineering), with a linear moving rate ranging between 0.5 and 2 mm/sec (Lu et al, 2005). The compression raises the medium to submerge the carriers, thus allowing for nutrient transfer.…”
Section: Bellocell Reactor Configuration and Operationmentioning
confidence: 99%
“…The BelloCell bioreactors have been successfully used to cultivate mammalian cells for the production of HDV-like particles [15], Japanese encephalitis virus [16], and insect cells for baculovirus [17]. In these studies, the bioreactors have consistently shown various beneficial characteristics: (1) Improved efficiency because they are pre-sterile and ready-to-use, (2) low shear stress because they move the liquid gently without the generation of gas bubbles, (3) large surface area to achieve a high-density growth of cells, and (4) the ability to collect whole cells or cell components [15, 18, 19]. At present, the use of these single-use bioreactors for influenza vaccine production has not been reported.…”
Section: Introductionmentioning
confidence: 99%